Experts speaking: Crucial teacher attributes for implementing blended learning in higher education - Bruggeman, Bram; Tondeur, Jo; Struyven, Katrien; Pynoo, Bram; Garone, Anja; Vanslambrouck, Silke (The Internet and higher education, 2021)
While blended learning in higher education is valued for various reasons such as addressing students' needs for flexibility, blended learning implementation remains a challenging process. Because the teacher lies at the heart of any educational change process, the current qualitative study investigates crucial teacher attributes for blended learning implementation from the perspective of experts. Experts can analyze deep structures of complex organizational problems and hold process knowledge that can generate practical effect. Twelve expert interviews are conducted and reveal two groups of blended learning teacher attributes: seven adaptive attributes such as realizing a pedagogical need for change or creatively connecting technologies to learning processes, and four maladaptive attributes such as a need for a clear understanding of blended learning or feeling anxious about (the implications of) technology. This study utilizes a holistic approach to identify related teacher attributes that critically influence the implementation of blended learning in higher education. •Two sets of related teacher attributes critically influence blended learning implementation in higher education.•Implementation of blended learning starts with realizing a pedagogical need for change.•Being able to creatively connect technologies to learning processes is essential.•A clear understanding of the pedagogical concept blended learning is a prerequisite.•Though challenging, expert interviews reveal rich process knowledge that has the power to produce practical effect.